Path analysis and the discrepancy evaluation model an approach to program evaluation - Umila, Benwardo V. (Education quarterly.)
This paper has attempted to apply the method of path coefficients to the analysis of the program design as laid out according to the Discrepancy Evaluation Method. The rationale is based on the assumption of functional dependencies of the program components. Path equations are formulated to translate the inter-relationships among the components. Path coefficients are then used to measures the strength of these functional dependencies. These coefficients become the bases for program design validation.